2019
DOI: 10.1007/s10792-019-01133-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ramadan daytime fasting with ocular surface inflammation and dry eye

Abstract: Purpose Despite the widespread practice of fasting, there are no studies looking at ocular surface inflammation, specifically matrix metalloproteinase 9 (MMP-9) testing, during fasting. In this prospective study, we wanted to evaluate the effect of Ramadan fasting on the level of tear film MMP-9 as well as other standard indicators of dry eye disease. Methods Forty healthy patients without history of ocular disease were tested before and toward the end of Ramadan. Each patient was assessed at each timepoint fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In this study, the decrease of MMP-9 was observed until T5. Unfortunately, there was no comparison study available in regard to MMP-9, except one that measured MMP-9 from the ocular surface ( 52 ). Furthermore, it seems the benefit of fasting in different diseases could be mediated by the decrease of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the decrease of MMP-9 was observed until T5. Unfortunately, there was no comparison study available in regard to MMP-9, except one that measured MMP-9 from the ocular surface ( 52 ). Furthermore, it seems the benefit of fasting in different diseases could be mediated by the decrease of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, a previous study reported no significant association between OSDI score and Ramadan fasting although they did not quantify the participants’ beverage intake. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al [56] evaluated Ramadan's fasting on the level of tear film matrix metalloproteinase-9 (MMP-9) and other standard indicators of dry eye disease in forty healthy patients without a history of ocular disease before and during Ramadan. Ocular Surface Disease Index scores, tear breakup time (TBUT), Schirmer I test, and corneal fluorescein staining were evaluated at each time point.…”
Section: Changes In the Structure And Function Of The Eye During Fastingmentioning
confidence: 99%